2006
DOI: 10.1038/ncprheum0216
|View full text |Cite
|
Sign up to set email alerts
|

Technology Insight: adult stem cells in cartilage regeneration and tissue engineering

Abstract: Articular cartilage, the load-bearing tissue of the joint, has limited repair and regeneration potential. The scarcity of treatment modalities for large chondral defects has motivated attempts to engineer cartilage tissue constructs that can meet the functional demands of this tissue in vivo. Cartilage tissue engineering requires three components: cells, scaffold, and environment. Adult stem cells, specifically multipotent mesenchymal stem cells, are considered the cell type of choice for tissue engineering, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
241
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(243 citation statements)
references
References 56 publications
1
241
0
1
Order By: Relevance
“…5,26 Numerous in vitro studies showed that primary MSCs undergo chondrogenic differentiation when cultured in the presence of specific media supplements, including dexamethasone and certain extracellular biological cues. 27,28 TGF-b1 has been used as a key inductor of chondrogenesis in many in vivo and in vitro studies, as it stimulates cell proliferation and synthesis of major components of ECM, GAG and collagen. [29][30][31] It was chosen for use in this study because it is one of the best characterized and most potent chondrogenic growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…5,26 Numerous in vitro studies showed that primary MSCs undergo chondrogenic differentiation when cultured in the presence of specific media supplements, including dexamethasone and certain extracellular biological cues. 27,28 TGF-b1 has been used as a key inductor of chondrogenesis in many in vivo and in vitro studies, as it stimulates cell proliferation and synthesis of major components of ECM, GAG and collagen. [29][30][31] It was chosen for use in this study because it is one of the best characterized and most potent chondrogenic growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…11 Adipose-derived mesenchymal stem cells (ADMSCs) have become a focus of research in recent years due to their similar multipotential properties, high responsiveness to distinct environmental cues, and ease of isolation. 12,13 Typically, adipose tissue is abundant in both humans and animals and can be easily harvested from subcutaneous tissue through percutaneous or limited open aspiration techniques. stromal cells when harvested compared to that of bone marrow.…”
mentioning
confidence: 99%
“…However, concerns associated with using autologous chondrocytes include injuries at the harvested site and their intrinsic tendency to lose phenotype during monolayer expansion. 1,2 Mesenchymal stem cells (MSCs) are considered the cell type of choice for their ability to differentiate into chondrocytes in a singlestep procedure without needing a biopsy/culture phase and staged re-implantation surgery. 3 A key for successful cartilage regeneration from MSCs is to correctly modulate cells to differentiate into the chondrogenic lineage and express normal cartilage extracellular matrix (ECM).…”
mentioning
confidence: 99%